Report on the Observance of Standards and Codes, Accounting and Auditing : Module A - Accounting and Auditing Standards, A.2 Auditing Standards Analysis - World Bank (World Bank, Washington, DC, 2017)
To a great extent, the quality of financial reporting depends on the quality of the Accounting and Auditing standards on which the reporting and auditing requirements are based. The objective of the auditing standards analysis is to compare the national standards used to conduct audits of historical information with International Standards on Auditing (ISA) with a view to capturing significant differences (where applicable) in order to provide counterparts with concrete suggestions for improving national standards and aligning them to the extent possible with international standards.